KAJIAN MANAJEMEN SUPPLY CHAIN DAN KETERKAITANNYA TERHADAP KETAHANAN PANGAN - Kamaruddin, Kamaruddin; Hamizar, Arizal (IAIN Ambon, 2022)
ABSTRACTThis research aims to analyze the relationship between supply chain management and food security. The method used in this research is a concept-based literature study. Relevant documents have been collected and analyzed to find findings related to this topic. The results of the research showed that supply chain management plays an important role in supporting food security, especially in terms of planning, organizing, controlling, monitoring and delivering food products. Supply chain management can also contribute to increasing productivity and quality of food products, optimizing food product distribution and ensuring food product availability in the market. In addition, supply chain management also helps to reduce total costs and increase operational efficiency.Keyword: Food Security, Management, Supply Chain. ABSTRAKPenelitian ini bertujuan untuk menganalisis keterkaitan manajemen supply chain dan ketahanan pangan. Metode yang digunakan dalam penelitian ini adalah studi pustaka yang berbasis konseptual. Dokumen yang relevan telah dikumpulkan dan dianalisis untuk mencari temuan yang berkaitan dengan topik ini. Hasil penelitian menunjukkan bahwa manajemen supply chain berperan penting dalam mendukung ketahanan pangan, terutama dalam hal perencanaan, pengorganisasian, pengendalian, pengawasan dan pengiriman produk pangan. Manajemen supply chain juga dapat berkontribusi terhadap peningkatan produktivitas dan kualitas produk pangan, serta mengoptimalkan distribusi produk pangan dan memastikan ketersediaan produk pangan di pasar. Di samping itu, manajemen supply chain juga membantu dalam mengurangi biaya total, meningkatkan efisiensi operasional.